Distribution of metals and persistent organic pollutants in selected shrimp species from five fish landing sites in Peninsular Malaysia / Noranis Ismail - Noranis , Ismail (2019)

(untitled)
The concentration of contaminants such as metals and persistent organic pollutants (POPs) in the marine ecosystem has become a major concern since it can accumulate within the food chain of marine life. In general, this study aimed to analyse the abundance of selected metals (Hg, As, Cu, Pb and Cd) and presence of selected POPs (dichlorodiphenyltri-chloroethanes and hexa-chlorocyclohexanes) in selected shrimp samples collected from fish landing sites in Peninsular Malaysia. This study also aimed to assess the quality of shrimp by comparing with the FAO/WHO Standard and Malaysian Food Act and Food Regulations 1983 (MFA). The concentration of metals in shrimp samples were used to calculate the estimated daily intake (EDI) of metals, target hazard quotients (THQ) and target cancer risk (TR) for locals. In this study, three selected shrimp species obtained from five fish landing sites located along the East and West Coast of Peninsular Malaysia were analysed using Inductively Couple Plasma-Mass Spectrophotometer (ICP-MS) for heavy metals while the analysis for POPs were performed using Gas Chromatography Electron-Capture Detector (GC-ECD). The highest concentration of As, Hg and Pb were detected in shrimp samples collected from Perak, which are P. merguiensis (328.93 + 0.78 μg/g), P. merguiensis (1012.83 + 0.78 μg/g) and P. monodon (4.07 + 1.31 μg/g), respectively. The highest concentration of Cu was found in L. vannamei (7.56 + 0.51 μg/g) collected from Malacca, whereas for Cd was found higher in L. vannamei (0.66 + 0.38 μg/g) collected from Johor. Significant difference was obtained between the accumulation of Pb in L. vannamei and Cd concentration in P. monodon for all sampling locations (p<0.05). Most of the values were higher than the permitted limit set by FAO/WHO 2010, as well as, the Food Act 1983 and Food Regulations 1985. From this study, it can be clearly seen that shrimps collected along the west coast of Peninsular Malaysia are more contaminated because of more industries and denser population, thus more contaminants were discharged. As for POPs, dichlorodiphenyltri-chloroethanes (DDT) is more abundant in the shrimp species compared to hexa-chlorocyclohexanes (HCH). It probably resulted from the excessive application of pesticides and disease control agents that contain DDT. It can be concluded that shrimp samples collected from Peninsular Malaysia are contaminated with selected metals and POPs.